(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
In this research work, cellulosic waste mango (Mangifera indica) saw dust used as the reinforcing material with low density polyethylene (LDPE). A number of samples of saw dust reinforced low density polyethylene (LDPE) composites were prepared by compression moulding technique. In order to improve the mechanical properties of saw dust-LDPE composites, unbleached raw saw dust fibers were modified by oxidation using sodium hypochlorite. FT-IR spectroscopic and scanning electron micrograph (SEM) analyses were done and the results showed the evidence of positive oxidation reaction. The effects of oxidized saw dust on the performance of oxidized saw dust reinforced LDPE composites were studied comparing with the raw saw dust-LDPE composites. The effects of fiber content on the physico-mechanical properties of composites were also studied by preparing the composites with different percentage of fiber loading (from 7.5 wt% to 30 wt%) for each type of composite. Mechanical properties such as tensile strength, tensile modulus, elongation at break, flexural strength, flexural modulus of the resulting composite were measured. Better results were obtained from oxidized saw dust-LDPE composites. Scanning electron micrograph and water absorption tests were carried out for all composites and improved results were found for oxidized saw dust-LDPE composites. Bangladesh J. Sci. Ind. Res. 47(4), 365-372, 2012 DOI: http://dx.doi.org/10.3329/bjsir.v47i4.14065